Training to build nutrition capacity in the Nigerian agricultural sector: Initial assessment and future directions - Adeyemi, O.; Phorbee, O.; Samuel, F.; Sanusi, R.; Afolabi, W.; Covic, Namukolo M.; Onabolu, A.; Ajieroh, V. (SAGE Publications, 2023)
In response to calls to increase nutrition-sensitive agriculture (NSA), the Federal Ministry of Agriculture and Rural Development developed the Nigeria Agricultural Sector Food Security and Nutrition Strategy 2016-2025 (AFSNS). Capacity development activities to facilitate the AFSNS implementation subsequently commenced.This study analyzed the processes and outputs of initial capacity development efforts, examined findings from the analysis using existing literature, and identified critical next steps for nutrition capacity development in the Nigerian agriculture sector.The study reviewed documents including a proposal for nutrition training of agriculture sector actors, reports of meetings held among 6 resource persons who designed and/or delivered training, training reports, participants’ pre- and posttraining assessments, and participants’ training evaluation. Interviews were conducted with 2 resource persons involved in training design and delivery. Documents and interviews were coded and analyzed to identify emergent themes. Participants’ pre- and posttests results were compared using paired t test in Stata 12.0.Knowledge and practice gaps were more extensive than had been anticipated. Training had some but limited effects on knowledge scores at the federal level. Modules addressing implementation practices had to be scaled down for participants to keep up with the learning pace. Existing literature indicates that such training would have been better planned as part of a broader sectoral nutrition workforce strategy, to facilitate greater tailoring of training to participants’ job roles.Effective AFSNS implementation requires developing and operationalizing a comprehensive short-, medium- and long-term Agriculture Sector Nutrition Capacity Development Strategy for Nigeria.